Answer:
B. ) x² + 4x + 3
Step-by-step explanation:
(f-g)(x) = f(x) - g(x) =
(2x²-5) - (x²-4x-8) =
2x² - x² + 4x + 8 - 5 =
x² + 4x + 3
Answer:
21.2
Step-by-step explanation:
Answer:
x = 1091.63315843
<span>
Setting Up:
7 = ln ( x + 5 )
ln translates to "log" with an "e" as the base or subscript ( a small "e" at the bottom right of the "g" in log).
You take the base of the log and put it to the power of "7" ( "7" is the natural log of ( x + 5 ) in this problem ).
The value of which the logarithm is calculated is set equal to the base of the logarithm to the power of the calculated logarithm of the value.
e^7 = x + 5
Solving</span>:
e = 2.71828182846
Natural logarithms are logarithms to the base of the constant 'e'.
e^7 = x + 5 ( simplify e^7 )
<span>1096.63315843 = x + 5
</span>
Subtract 5 from each side.
1091.63315843 = x
The product of a non-zero rational number and an irrational number is irrational.
Therefore C is the answer.
A, B, and D are all properties of rational numbers. Irrational numbers are ones that can not be written as a ratio, or fraction, using whole numbers. They are non-repeating, non-terminating numbers. Example would be pi.
Answer:
b) c + 0.35c − 10
Step-by-step explanation: